Effects of multiple agroecological interventions on crop nutrient acquisition and performance - Ritcey-Thorpe, Leah; Fulthorpe, Roberta R.; Isaac, Marney E. (Frontiers in Sustainable Food Systems, 2025)
With the growing focus on agroecological interventions in crop production, more studies are required to understand the combined effects of multiple strategies on soil and plant health. In this study, we adopted a functional-trait approach to evaluate the resource acquisition strategies of crops in response to an organic amendment and a growth-promoting endophytic bacterial seed inoculant. Using wheat and soybean as model crops, we assessed crop performance traits [leaf chlorophyll (μmol m−2), base diameter (mm), biomass (g), nitrogen (N) usage index] and root traits [specific root length (SRL, m g−1), specific root tip density (SRTD, tips g−1), root diameter (root D, mm), root tissue density (root TD, g cm−3), root nitrogen (root N; %), root carbon-to-nitrogen ratios (root C/N)], along with the chemical and biological properties of rhizosphere soil at the end of the growing season. We employed three soil amendment treatments (organic, inorganic, and control) and two seed inoculant treatments (with and without seed inoculation). Soil amendments influenced the expression of wheat root traits, promoting acquisitive root traits—characterized by higher SRL, SRTD, and root N, along with lower root D—under organic amendments. There was no impact of soil amendments on soybean root trait expression. In contrast, seed inoculation positively affected the performance traits of base diameter and the nitrogen usage index of wheat. The significant interactive effects of soil amendments and seed inoculation were minimal. In the rhizosphere soil of wheat and soybeans, available phosphorus was significantly lower with organic amendments, while active carbon (POxC) was significantly higher with organic amendments for wheat. Well-established significant relationships between soil properties and root traits were also evident. Correlations between root traits and rhizosphere properties were apparent, specifically positive correlations between POxC and SRL, and negative correlations with the root C/N ratio. The composition of the rhizosphere soil fungal community was significantly explained by key root traits, including root D and root C/N ratio. Broadly, soil amendments had a stronger impact on crop root responses than seed inoculants, yet seed inoculants influenced direct measures of crop performance. Importantly, these two agroecological interventions did not significantly interact, indicating opportunities for better integration of agroecological strategies.